Numerical solutions of stochastic differential equations - Ben Dnaidina, Imane; Boukehila, Ahcene, Directeur de thèse (Laghouat : Université Amar Telidji - Département de mathématiques, 2024)
”Numerical Solutions of Stochastic Differential Equations” refers to approximating solutions of equations involving randomness. This approach uses analytical and probabilistic mathematics to find digital solutions to complex equations that change randomly over time.